Subsequent Surgery and Prevalence of Osteoarthritis Following Arthroscopic Meniscus Posterior Root Repair: Association with Patient Age and Body Mass Index. Issue 7 (21st July 2017) - Lamplot, Joseph D.; Lillegraven, Olivia; Wojahn, Robert D.; Brophy, Robert H.
Objectives: Posterior meniscus root tears disrupt the tibial plateau attachment, leading to a loss of hoop stresses and significant increases in tibiofemoral contact forces. As a result, there is growing interest in surgical repair of these tears. The purpose of this study is to report rates of recurrent surgery and prevalence of osteoarthritis following posterior meniscus root repairs, and associated patient factors, in a North American population. Methods: Arthroscopic posterior meniscus root repair using a pullout trans-tibial suture method was performed by a single surgeon in the United States. Eligible patients d the Knee Injury and Osteoarthritis Outcome Score (KOOS) and reported any subsequent surgeries at minimum two-year follow-up. Patients were categorized as having clinical OA based on their KOOS score. When available, post-operative radiographs were evaluated for radiographic OA using the Kellgren-Lawrence classification and the OA Research Society International (OARSI) atlas. The association of factors with the incidence of clinical and radiographic OA was evaluated. Results: Follow up was collected on 28 of 32 eligible patients (87.5%) at a mean follow up of 2.46 years (range 2.05-3.76 years). At time of surgery, mean age was 44.6 years and mean BMI was 32.7. At follow-up, two patients had undergone subsequent surgery (7%). 14 patients (50.0%) met KOOS criteria for clinical OA. Among the 11 patients with available follow up radiographs, 4 (36%) met OARSI atlas criteria for knee OA. For medial posterior root tears, patients over the age of 45 with BMI over 35 were significantly more likely to develop clinical (85.7% versus 35.0%, p=0.033) and radiographic OA (80.0% versus 0.0%, p=0.015), and undergo additional surgery (40% versus 0%, p=0.036). Conclusion: Arthroscopic repair of posterior root tears in a North American population has a low rate of subsequent surgery despite developing clinical and radiographic OA. Older and heavier patients have a higher incidence of clinical and radiographic OA. Further study is needed to determine optimal treatment for root tears in these patients. KOOS scores by patient group KOOS score All patients (mean, 95% CI) Medial meniscal root tear only ACL and meniscal root tear p-value KOOSpain 84.0 (67.6-100) 83.3 (70.4-96.2) 91.3 (80.6-100) 0.197 KOOSsymptoms 79.4 (57.1-99.7) 79.3 (52.3-100) 85.6 (73.9-97.4) 0.478 KOOSADL 88.4 (72.2-100) 86.2 (68.7-100) 98.3 (95.8-100) 0.022 KOOSsport/rec 65.6 (33.4-97.7) 60.7 (34.2-87.1) 83.1 (67.8-100) 0.219 KOOSQoL 66.6 (39.9-93.4) 64.6 (50.0-79.4) 81.3 (65.5-100) 0.107 KOOStotal 381.0 (277.2-484.7) 373.1 (303.4-442.9) 440.1 (385.7-494.5) 0.105